Diplomatic Protection of the state citizens out of the country - Hamid Selim, Dr. Suha (The college of law and political science journal, 2023)
to state the allows that system legal international an ,protection Diplomatic host the in harm caused have interests whose citizens its of cases the adopt belongs who individual the of behalf on and state the of right the is it and ,country International establishing after damage the repair or compensation demand to it to the time the at nationality its of enjoyment their confirming and ,responsibility .required is exhaustion the and ,him to occurs harm personally having not as well as ,remedies domestic all has individual The